2017
DOI: 10.3389/fpsyg.2017.01054
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Direct Instruction and Strategy Modeling on Upper-Primary Students’ Writing Development

Abstract: Strategy-focused instruction is one of the most effective approaches to improve writing skills. It aims to teach developing writers strategies that give them executive control over their writing processes. Programs under this kind of instruction tend to have multiple components that include direct instruction, modeling and scaffolded practice. This multi-component nature has two drawbacks: it makes implementation challenging due to the amount of time and training required to perform each stage, and it is diffi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0
12

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
1

Relationship

4
5

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 39 publications
1
12
0
12
Order By: Relevance
“…There is evidence from interventions with older children to support both of these positions (Fidalgo et al, 2015;López et al, 2017;Sawyer et al, 1992). Application of the full program implemented in the present study is relatively time-consuming and effortful, and omitting redundant components is desirable.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is evidence from interventions with older children to support both of these positions (Fidalgo et al, 2015;López et al, 2017;Sawyer et al, 1992). Application of the full program implemented in the present study is relatively time-consuming and effortful, and omitting redundant components is desirable.…”
Section: Discussionmentioning
confidence: 99%
“…We implemented and evaluated a strategy-focused instructional program with mixedability classes of Spanish children in the second trimester of their 1st grade. The intervention was based in Cognitive Self-Regulation Instructiona strategy-focused approach to writing instruction similar to SRSD -that has been demonstrated to have positive and sustained effects in 6 th grade children (Fidalgo, Torrance, & García, 2008;Fidalgo, Torrance, Rijlaarsdam, van den Bergh, & Álvarez, 2015;López, Torrance, Rijlaarsdam, & Fidalgo, 2017;Torrance et al, 2007). Writing performance was evaluated in controlled tasks prior to intervention, immediately following intervention, and at seven weeks.…”
Section: Introductionmentioning
confidence: 99%
“…Differences in both procedures and products obtained while engaging in reading–writing tasks, such syntheses and argumentative texts, have been documented in students at different educational levels (Mateos & Solé, ; Spivey & King, ). Even young students, however, are required to understand and produce different text genres, including continuous and non‐continuous argumentative texts, presented both in print and digitally (MIUR, ; see also Barzilai et al ., ; López, Torrance, Rijlaarsdam, & Fidalgo, ). Therefore, it is likely that students at this educational level possess basic knowledge on how to write an argumentative short essay, if texts appropriate for complexity are presented.…”
Section: Introductionmentioning
confidence: 99%
“…Writing instruction in this educational stage should, therefore, focus on self-regulation strategies which allow students to structure and organize their texts (Zimmerman & Bandura, 1994). Several studies have demonstrated the efficacy of strategy-focused writing instruction with upper-elementary students (Fidalgo, Torrance, & García, 2008;Fidalgo, Torrance, Rijlaarsdam, van den Bergh, & Álvarez, 2015;López, Torrance, Rijlaarsdam, & Fidalgo, 2017;Torrance, Fidalgo & García, 2007). These previous empirical evidences provide the background to the Intelligent Tutor System design.…”
Section: Participantsmentioning
confidence: 99%